Intraoperative Puncture of the Retina. Clinical Case - N. M. Kislitsyna; A. A. Zasypkina; D. M. Sultanova (Oftalʹmologiâ)
Clinical case present of a complication of retrobulbar anesthesia and a method of its treatment in the practice of a vitreoretinal surgeon. A technique for closing a retinal defect caused by a needle puncture during retrobulbar anesthesia with a flap of the internal limiting membrane is presented. Stages of the operation: A vitrectomy was performed in full, with the closure of the macular hole using the inverted flap method and punctures of the retina with the inner boundary membrane, previously stained with the Vitreocontrast suspension, were detected. The operation was completed by successive replacement of physiological saline with a gasair mixture 20% С3F8 (3 ml). As a result of successful surgical treatment, the macular hole and retinal punctures were closed with an internal limiting membrane.